PENDAMPINGAN PENCATATAN KEUANGAN DIGITAL (PENERIMAAN KAS) DI TK PERMATA - Dony Waluya Firdaus; Ghazwan Rifat Al-Faris (Indonesian Community Service and Empowerment Journal (IComSE), 2026)
The Community Service and Empowerment (P2M) program aims to provide assistance to Permata Kindergarten in implementing a digital-based financial recording system. Currently, recording at Permata Kindergarten is still manual, using paper/books to record receipts and expenditures. This manual recording is prone to errors and loss of books. The mentoring method at Permata Kindergarten is based on analysis, observation, interviews, and an educational and participatory approach to assess the situation and conditions of the partner, Permata Kindergarten. The P2M team provides mentoring, outreach, and training, focusing on cash receipts. The mentoring is conducted using simple software such as spreadsheets or cloud-based accounting applications. This digitalization of recording aims to simplify the automatic calculation process and reduce errors. With a digital financial recording system, Permata Kindergarten can record payments, create financial reports accurately and quickly, and monitor student payment status in real time. The implementation of this digital system is expected to improve the accuracy of financial management, which is crucial for building parental trust.